Analisis Gaya Kepemimpinan Kepala Sekolah Dalam Meningkatkan Kinerja Guru Di SD Negeri Singopuran 02 Kartasura Tahun 2016/2017 - Prasetyo, Hervian; , Honest Ummi Kaltsum, S.S., M.Hum (2017)
This research is aimed to describe 1. analysis of principal leadership style in improving teacher performance in SD Negerti Singopuran 02 Kartasura. 2. Headmaster Barriers in improving teacher performance and 3. principal's solution in improving teacher performance. This research is a qualitative research with analytic descriptive approach. The collecting data teachnique used are interview, observation, and documentation. Data validity was checked using triangulation method and source triangulation. The data analysis technique used is interactive analysis technique which consist of data reduction, data explanation, and conclusion & verification. Based on the research results can be concluded that 1. The leadership style of principals in improving teacher performance in SD Negeri Singopuran 02 leads to a democratic leadership style. 2. Obstacles in improving teacher performance ranging from discipline, responsibility, and how to teach and 3. Solutions from the principal is to make a schedule picket, assign tasks to teachers, and always provide encouragement and motivation to all teachers. Keyword:leadership sytle, headmaster, performance of teacher